HOSPITAL IMAGE FORMATION: ASSESING THE EFFECT OF WEBSITE AND SERVICE QUALITY AS MEDIATED BY PATIENT SATISFACTION - Yusuf Gunawan; Felina Young; Lilia Chio; Sionnida Baes; Robert Y. Co; Hector Manaligod; Arvel Hafiza A. Yusuf (JTH: Journal of Technology and Health, 2026)
With patient satisfaction as a mediating variable, this study investigates how website quality and service quality influence patient perceptions of hospitals. Conducted at Dr. Slamet Public General Hospital in Garut, Indonesia, the research employs a quantitative, explanatory design using structural equation modeling (SEM) to analyze data from 385 respondents. Website quality WEBQUAL is measured across seven dimensions usability, content, design, functionality, service interaction, trust, and interactivity while service quality is assessed using the SERVQUAL model. Patient satisfaction encompasses experience, communication, and accessibility, and hospital image includes perceived care quality, trust, brand reputation, and information accessibility. The results demonstrated that both website quality and service quality significantly enhance patient satisfaction. In turn, patient satisfaction positively influences hospital image, and also mediates the effects of website and service quality on hospital image. The study concludes that digital touchpoints, particularly hospital websites, play a strategic role in shaping patient perceptions and institutional reputation. Practical implications suggest that hospitals should integrate digital optimization with service excellence to foster patient satisfaction and build a competitive image. Limitations include the study’s cross-sectional design and localized scope, with recommendations for broader sampling and longitudinal analysis in future research.